Capnography and Pulse Oximetry Improve Fast Track Extubation in Patients Undergoing Coronary Artery Bypass Graft Surgery: A Randomized Clinical Trial - Moradian, Seyed Tayeb; Beitollahi, Fatemah; Ghiasi, Mohammad Saeid; Vahedian-Azimi, Amir (Frontiers in Surgery, 2022)
Background: Use of capnography as a non-invasive method during the weaning process for fast track extubation (FTE) is controversial. We conducted the present study to determine whether pulse oximetry and capnography could be utilized as alternatives to arterial blood gas (ABG) measurements in patients under mechanical ventilation (MV) following coronary artery bypass graft (CABG) surgery. Methods: In this randomized clinical trial, 70 patients, who were candidates for CABG surgery, were randomly assigned into two equal groups (n=35), intervention and control group. In the intervention group, the ventilator management and weaning from MV was done using Etco2 from capnography and SpO2 from pulse oximetry. Meanwhile, in the control group, weaning was done based on ABG analysis. The length of intensive care unit (ICU) stay, time to extubation, number of manual ventilators setting changes, and alarms were compared between the groups. Results: The end-tidal carbon dioxide (ETCO2) levels in the intervention group were completely similar to the partial pressure of carbon dioxide (PaCo2) in the control group (39.5±3.1 vs. 39.4±4.32, P>0.05). The mean extubation times were significantly shorter in the intervention group compared to those in the control patients (212.2±80.6 vs. 342.7±110.7, P<0.001). Moreover, the number of changes in the manual ventilator setting and the number of alarms were significantly lower in the intervention group. However, the differences in the length of stay in ICU between the two groups were not significant (P=0.219). Conclusion: Our results suggests that capnography can be used as an alternative to ABG. Furthermore, it is a safe and valuable monitor that could be a good alternative for ABG in this population. Further studies with larger sample sizes and on different disease states and populations are required to assess the accuracy of our findings.